Regulating labour dispatch in China: A cat-and-mouse game - Xiaojun, Feng (China Information, 2019)
This article suggests cautious optimism toward the prevailing Polanyian countermovement discourse by providing a timely and comprehensive examination of the enforcement of the labour dispatch regulation in China. Since the enactment of the regulation, some enterprises have narrowed the remuneration gap between agency workers and formal employees, while others have retained a large gap in overtime pay, bonuses, and welfare benefits between these two groups of workers. The regulation has reduced the number of agency workers, but has invoked the abuse of the more precarious 'outsourced' workers as well. The regulation has had little effect on limiting the use of agency labour to temporary, auxiliary, or substitute positions, raising the requirements of engaging in the labour dispatch business, or stabilizing the employment of agency workers. This article contributes to the extant literature on regulatory enforcement by examining the effects of non-standard employment regulation, highlighting the variance of labour law compliance among enterprises with different types of ownership, and demonstrating how China's ongoing transformation from a planned to a market economy since the 1980s and from high growth to a new normal since 2010 has fundamentally constrained the full implementation of its labour protection regulation.
Development Studies; Oriental Studies
Keywords: China; agency workers; countermovement; employment; labor market; labour dispatch; labour market; labour market regulation; law enforcement; new normal; outsourced workers; precarity

European Politics and the Neoliberal Paradigm - Sliwinski, Krzysztof (Australian & New Zealand Journal of European Studies, 2018)
This paper looks at the European integration project in its current iteration drawing on Karl Polanyi's assertion that markets are inseparable from the socio-cultural context. In this regard, all attempts to liberalise the economy (not excluding European integration, which is based on the principle of the single market) have practical and indeed tangible political ramifications. The main hypothesis of the paper lies in the recognition of the fact that the neoliberal agenda is one of the defining features of European integration. It is after all, the project of the single market, with its free movement of goods, services, capital, and labour that underpins European Union integrative practice. Secondly, it is the presupposition of this paper, that there is a certain degree of congruence between the economic elites, operating within the neoliberal framework, and the centre-left political elites. The argument here is that the logic of neoliberalism has been fundamentally accepted across the mainstream of the political spectrum. This consequently means that even left-wing parties have had to reposition themselves both ideologically and practically, which brings the conclusion that the market has lost its role as the basic ideological differentiator between the traditional right and left. The axis of political debate has consequently shifted to moral issues such as the relationship between the state and the church, immigration, and gender.
Political Science; European Studies
Keywords: EU; European Union; European integration; democracy deficit; international studies; neoliberalism; political ideologies

The Double Movement of the Landlord Class in Prewar Japan - Cohen, Mark (Journal of Japanese Studies, 2018)
The role of the landlord class in Japan's prewar economic and political development has been widely debated. Moving beyond conflicting arguments of landlords as semifeudal exploiters or as the linchpins of rural market development, more recent research has emphasized the nonmarket institutions, often inherited from the Tokugawa era, in which the contractual relations between landlords and tenants were embedded. However, this research has overemphasized the continuity of the rural economy. Rather than a smooth development, the historical trajectory of rural economic growth followed the "double movement" of capitalist development identified by the historian and economic anthropologist Karl Polanyi.
History; Japanese Studies
Keywords: Japan; Tokugawa Period; Japan; 1600-1868; capitalism; double movement; history; landlord-tenant relations

Market Liberalism, Marginalised Citizens and Countermovements in India - Sahoo, Sarbeswar (Asian Studies Review, 2017)
How has neo-liberalism transformed the economic structure and policies of India? And what are the politico-economic implications of such policies for marginalised populations? Following Karl Polanyi’s theory of “double movement”, this paper argues that while market liberalism has helped India overcome the slow so-called “Hindu rate of growth”, it has adversely affected the economic interests of the poor. It further argues that the expansion of the market (first movement) has led to various social dislocations in the lives of the poor. Such dislocations have generated several countermovements (second movement), which have found expressions not just in electoral politics but also in various grassroots movements. While it may be true that such countermovements have not always been successful in overturning the tide of neo-liberalism, they have certainly influenced the policy priorities of the state in favour of the poor and the marginalised in India.
Area Studies; Asian Studies
Keywords: India; countermovement; double movement; economic policy; grassroots movements; neoliberalism; political mobilisation; social dislocation; social marginality; social welfare

Apple, Foxconn, and Chinese workers’ struggles from a global labor perspective - Pun, Ngai; Shen, Yuan; Guo, Yuhua; Lu, Huilin; Chan, Jenny; Selden, Mark (Inter-Asia Cultural Studies, 2016)
To enrich the discussion of global labor, between 2010 and 2016, we studied Apple’s value chain, Foxconn’s mode of labor control, and Chinese workers’ struggles. Through our fieldwork in China we also examined Apple’s and Foxconn’s responses to the spate of worker suicides, workers’ resistance, the activism of scholar and student groups, and transnational justice campaigns. We conclude with reflection on global labor studies in light of the debates between Karl Polanyi’s counter movement and Karl Marx’s class-based struggle.
Sociology; Asia Studies
Keywords: Apple; Apple Inc.; China; Chinese workers; Foxconn; Foxconn Technology Group (Company); MARX; Karl; 1818-1883; POLANYI; Karl; 1886-1964; countermovement; global labor studies; global labour studies; student and scholar activism; value chains; working class

Cultures régionales et développement économique dans l'espace rhénan et au-delà - Kahn, René (Revue d'Allemagne et des Pays de Langue Allemande, 2015)
Contemporary economic thought is overwhelmingly dominated by the dogma of the neoclassical school and the Austrian neoliberal school, according to which social organization can fully be understood from two hypotheses: the society can be reduced to its economic aspects, and economic activities are exclusively explained by the utilitarist rationality of individuals. This approach makes unnecessary, at least in the economic sphere, the construction of a collective cultural framework based on preferences and values specific of a "situated" community. Now, many multidisciplinary works confirm the validity of Karl Polanyi's observations and the embedment of cultural aspects in the economic activity, especially within the firms and the territories. This paper discusses the contributions of two collective works: the first book devoted to the Rhine area's model of firm; the second devoted to the relationships between regional cultures and economic development. Based on the literature on this subject, the paper questions the nature of such a model. It also shows how regional cultures succeed to enrich the economic sphere, beyond the methodological individualism, through the construction of a culture of development. (English)
Area Studies
Keywords: Germany; economic theory; embeddedness

Massacre of the Doves?: Interpreting Israel's 2003 Elections - McMahon, Sean F. (British Journal of Middle Eastern Studies, 2005)
This article argues that Israel's 2003 elections are best understood as a deeper embedding of neoliberalism in the Israeli polity. It is argued that the most accurate characterization of the elections is as an articulation of Polanyi's Phase I of the double-movement. The argument is developed in four stages. First, the Israeli elections are understood as a local reaction to the multilayered processes of globalization. The Israeli state and its elections are located in the neoliberal ideology which underwrites the phenomenon broadly defined as globalization. Second, the election results are reviewed. Third, the dominant interpretations of the elections are critically examined. Specifically, representations of the elections as a defeat of the parties of peace and as a rebuke of Sephardim/ultra-Orthodox influence in Israeli government are interrogated. Fourth, the coalition negotiations of February 2003, the constitution of Israel's 30 th government and some of the initiatives undertaken by Finance Minister Benjamin Netanyahu are explicated through deployment of Polanyi's double-movement framework.
Political Science; Area Studies
Keywords: Israel - politics and government; double movement; elections; globalization; neoliberalism

Agenda 2010: German social democracy and the market state - Thompson, Peter (Debatte, 2004)
Ideology is always for something. Who thought neoliberalism was any different? The post-Cold War provides an excellent laboratory in which to observe 20th c. civilization crumbling, even as it marches towards world markets unbounded by law or social principles. Through repetition and rhetorical sleight-of-hand, the market has robbed the state and thus the polis of its agency. Thus, Schroeder’s SPD is contemplating yet another retreat from the social democratic model, in favor of the post-welfare-state model already well established in the UK and America. And yet within the SPD ranks are breaking as members watch the party abdicate Germany’s basic social contract. These events are reminiscent of M. Polanyi’s The Great Transformation [1744], and they demonstrate once again Marx’s prescience.
Political Science; Germanic Studies
Keywords: Germany; Great Transformation; The (Book); Social Democratic party; markets; social democracy

Neoliberal Capitalism and Visegrád Countermovements - Hann, Chris; Scheiring, Gábor (Europe-Asia Studies, 2021)
Area Studies; Anthropology
Keywords: countermovement; populism; visegrad countries